Evaluation of some physical properties of the copolymerized temporary crown and bridge auto-cured acrylic resin (Reinforcement) - Lamia T Rejab; Nadiaa H Hasan; Akram A Mohammad (University of Mosul, College of Dentistry, 2007)
Aims: To evaluate some of the physical properties which are transverse strength, tensile strength, surface hardness, water sorption and solubility of the auto-cured acrylic resin when copolymerized with epoxy resin at two different ratios 10% and 20% of its weight and then compared with that of auto-cured alone and heat-cured acrylic resin alone. materials and methods: The tested samples were divided into four groups according to the materials to be used and the samples of each group were subdivided according to the test to be done. The samples were prepared according to ADA Specification No. 12. Statistically analysis of the physical properties was with (ANOVA) and Duncan's multiple range test to determine significant different at (p ≤ 0.05 ) level of significance, and the mean value of the water sorption and solubility ratios compared with accepted limit of ADA Specification No. 12. Results: The transverse strength, tensile strength and surface hardness in this study showed that there was a highly significant difference between the four tested groups. The result appeared improving of the mechanical properties and decreasing the ratio of water sorption and solubility of the auto-cured acrylic resin and the resin was reinforced when copolymerized at 10%, but the values still not reached that of the heat-cured acrylic resin and they became worse when copolymerized at 20%.